B cells imprint adoptively transferred CD8+ T cells with enhanced tumor immunity. Issue 1 (11th January 2022) - Smith, Aubrey S; Knochelmann, Hannah M; Wyatt, Megan M; Rangel Rivera, Guillermo O; Rivera-Reyes, Amalia M; Dwyer, Connor J; Ware, Michael B; Cole, Anna C; Neskey, David M; Rubinstein, Mark P; Liu, Bei; Thaxton, Jessica E; et al.
Abstract : Background: Adoptive T cell transfer (ACT) therapy improves outcomes in patients with advanced malignancies, yet many individuals relapse due to the infusion of T cells with poor function or persistence. Toll-like receptor (TLR) agonists can invigorate antitumor T cell responses when administered directly to patients, but these responses often coincide with toxicities. We posited that TLR agonists could be repurposed ex vivo to condition T cells with remarkable potency in vivo, circumventing TLR-related toxicity. Methods: In this study we investigated how tumor-specific murine CD8 + T cells and human tumor infiltrating lymphocytes (TILs) are impacted when expanded ex vivo with the TLR9 agonist CpG. Results: Herein we reveal a new way to reverse the tolerant state of adoptively transferred CD8 + T cells against tumors using TLR-activated B cells. We repurposed the TLR9 agonist, CpG, commonly used in the clinic, to bolster T cell—B cell interactions during expansion for ACT. T cells expanded ex vivo from a CpG-treated culture demonstrated potent antitumor efficacy and prolonged persistence in vivo. This antitumor efficacy was accomplished without in vivo administration of TLR agonists or other adjuvants of high-dose interleukin (IL)-2 or vaccination, which are classically required for effective ACT therapy. CpG-conditioned CD8 + T cells acquired a unique proteomic signature hallmarked by an IL-2Rα high ICOS high CD39 low phenotype and an altered metabolic profile, all reliant on B cells transiently present in the culture. Likewise, human TILs benefitted from expansion with CpG ex vivo, as they also possessed the IL-2Rα high ICOS high CD39 low phenotype. CpG fostered the expansion of potent CD8 + T cells with the signature phenotype and antitumor ability via empowering a direct B–T cell interaction. Isolated B cells also imparted T cells with the CpG-associated phenotype and improved tumor immunity without the aid of additional antigen-presenting cells or other immune cells in the culture. Conclusions: Our results demonstrate a novel way to use TLR agonists to improve immunotherapy and reveal a vital role for B cells in the generation of potent CD8 + T cell-based therapies. Our findings have immediate implications in the clinical treatment of advanced solid tumors.